X chromosome‐linked long noncoding RNA lnc‐XLEC1 regulates c‐Myc‐dependent cell growth by collaborating with MBP‐1 in endometrial cancer. Issue 4 (23rd February 2019) - Li, Fang; Li, Hua; Zhang, Liyuan; Li, Wei; Deng, Jieqiong; An, Mingxing; Wu, Siqi; Lu, Xiaoxiao; Ma, Rui; Wang, Yirong; Guo, Binbin; Lu, Jiachun; et al.
Abstract : LncRNAs (long noncoding RNAs) are noncoding transcripts that are more than 200 nt long and have been described as the largest subclass in the noncoding transcriptome in humans. Although studies of lncRNAs in cancer have been continuing for a long time, no much has been known about X chromosome‐linked lncRNAs. Here, by using RNA‐seq we report the identification of a new X chromosome‐linked lncRNA ( lnc‐XLEC1 ) that is aberrantly downregulated during the development of endometrial carcinoma (EC). The overexpression of lnc‐XLEC1 reduces the migration and proliferation of EC cells. Flow cytometry analysis indicated that lnc‐XLEC1 overexpression resulted in a substantial accumulation of EC cells in the G1 phase. In addition, lnc‐XLEC1 had inhibitive effects that may result from its collaboration with MBP‐1 during the suppression of the c‐Myc expression and the negative regulating of the Cdk/Rb/E2F pathway. The anti‐tumor effects of lnc‐XLEC1 on EC progression suggest that lnc‐XLEC1 has some potential value in anti‐carcinoma therapies and deserves further investigation. Our study reported for the first time that the lnc‐XLEC1 might be related to the incidence and prognosis of EC. Moreover, we discovered that this process might be related to somatic X dosage compensation and skewed X chromosome inactivation (SXCI). Abstract : What's new? A newly identified X‐linked long noncoding RNA may affect endometrial cancer. Long noncoding RNAs (lncRNAs) have been implicated in regulatory roles in various malignancies. These authors used RNA‐seq to search for lncRNAs on the X chromosome involved in endometrial cancer. They successfully identified one, lnc‐XLEC1, which is downregulated in human EC tissue. They then demonstrated that overexpression of lnc‐XLEC1 slows cell proliferation and tumor growth. Next, they searched for proteins interactions, and found evidence that lnc‐XLEC1 suppresses c‐Myc by way of binding to MBP‐1. Thus, lnc‐XLEC1 could find a use as a therapy against endometrial tumors.